Building on research evidence to change health literacy policy and practice in England. (March 2015) - Rowlands, Gillian; Berry, Jonathan; Protheroe, Joanne; Rudd, Rima E.
Abstract : Background: Health literacy is important because of the high proportion of the population with skills below those needed to become and stay healthy, and the resultant negative impact on people's lives. A recent study in England has shown that, as is true in other industrialized nations, a significant proportion of people (43–61%) have literacy and numeracy skills below those needed to fully understand and use health materials. This paper describes a project designed to build on these findings with key stakeholders to develop an action plan to address a mismatch between population skills and the health system complexity. Method: The multi-stage project involved an initial meeting of stakeholders that allowed participants to share knowledge and experience, and make suggestions for change. Subsequent web-based surveys enabled widening of the stakeholder group, identification of further potential actions, and participant rating of the impact of the suggested actions on this mismatch. Next, a meeting enabled the group to identify priorities for change that would be feasible and cost-effective. Results: Forty-one participants were recruited from a range of patient, health, lifelong learning, civil service, and industry perspectives. Suggested topics for action fell into four areas; improving health services, building health literacy skills in the population and workforce, recognizing the importance of public information developed outside the health arena, and funding for health literacy research and development. Following consideration of likely cost, impact, and feasibility, five suggested areas were prioritized for action, three involving improvements in the health service, and two involving the development of public health literacy skills. The importance of inter-sectoral approaches to this complex issue was identified. Discussion: This project recruited key stakeholders with a wide range of relevant expertise and perspectives. It resulted in a clear, coherent action plan to address the population skills: health system complexity mismatch. Next steps include implementation, evaluation, and widening to other areas of life important to public health and well-being such as public safety messages and social care.